Social Isolation in Early versus Late Adolescent Mice Is Associated with Persistent Behavioral Deficits That Can Be Improved by Neurosteroid-Based Treatment - Locci, Andrea; Geoffroy, Philippe; Miesch, Michel; Mensah-Nyagan, Ayikoe-Guy; Pinna, Graziano (Frontiers in Cellular Neuroscience, 2017)
Early trauma and stress exposure during a critical period of life may increase the risk of major depressive disorder (MDD) and post-traumatic stress disorder (PTSD) in adulthood. The first-choice treatment for MDD and PTSD are selective serotonin reuptake inhibitor (SSRI) antidepressants. Unfortunately, half of MDD and PTSD patients show resistance to the therapeutic effects of these drugs and more efficient treatments are essential. Both MDD and PTSD patients present reduced levels of allopregnanolone (Allo), a potent endogenous positive allosteric modulator of GABA action at GABAA receptors (GABAARs), which are normalized by SSRIs in treatment responders. Thus, Allo analogs or drugs that stimulate its levels may offer an alternative in treating SSRIs-non-responders. We tested several drugs on the aggressive behavior of early and late adolescent socially-isolated (SI) mice, a model of PTSD. Isolation in early adolescence (PND 21) induced more severe aggression than mice isolated at PND 45. A single non-sedating administration of S-fluoxetine (S-FLX; 0.375-1.5 mg/kg), or of the Allo analogs ganaxolone (GNX; 10 mg/kg), BR351 (1-5 mg/kg), or BR297 (0.3125-2.5 mg/kg), or of the endocannabinoid, N-palmitoylethanolamine (PEA; 5-20 mg/kg) all decreased aggression more effectively in late than early adolescent SI mice. Importantly, the number of drug non-responders was higher in early than late SI mice for all the drugs tested. The non-responder rate was more elevated (12-64%) after S-FLX treatment, while 100% of mice responded to a single administration of PEA at the dose range of 15-20 mg/kg. Moreover, GNX, BR351 and BR297's antiaggressive effect persisted longer than S-FLX in both late and early SI mice. All drugs tested failed to alter locomotor activity of SI mice. Our results show that drugs that mimic Allo’s action or that induce Allo biosynthesis may be valuable for the treatment of "SSRIs non-responder" patients.